Selective Copper Recovery with HCl Leaching from Copper Oxalate Material - Sari, Z. Abidin; Turan, M. Deniz; Nizamoglu, Hasan; Demiraslan, Aslihan; Depci, Tolga (Springer Heidelberg, 2020)
In this study, recovery of copper from solid material (obtained by leaching of chalcopyrite with oxalic acid in the presence of hydrogen peroxide) with a copper oxalate structure was carried out selectively using HCl. The chemical composition of the solid was as 29.3%, 9.7%, and 13.3% for Cu, Fe, and S, respectively. Selective recovery of copper by degrading the copper oxalate structure with a low-solubility product (Ksp = 4.43 x 10(-10)) was performed by conventional leaching in the presence of HCl. The optimum leaching conditions were determined as 5 M of HCl concentration, 318 K of leaching temperature, 120 min of leaching time, 25 ml/g of liquid-solid ratio and 400 rpm of stirring speed. Under these conditions, approximately 77% of copper and 3% of iron were taken into the solution. According to the characterization of the leach residue that was obtained, the oxalate structure was degraded. Moreover, the results of XRD analysis showed that the sulfur (S) and cubanite (CuFe2S3) phases were mostly observed in leaching residues, and this was supported by the SEM-EDX data. Based on the results, it may be stated that selective copper extraction can be obtained from a chalcopyrite concentrate by a two-step leaching method using a conventional hydrometallurgical technique.
Keywords: Selectivity; Dissolution